Agile web development with Rails 6 - Ruby, Sam; Copeland, David (David Bryant); Thomas, David, 1956- (Pragmatic programmers., 2020)
"Learn Rails the way the Rails core team recommends it, along with the tens of thousands of developers who have used this broad, far-reaching tutorial and reference. If you're new to Rails, you'll get step-by-step guidance. If you're an experienced developer, get the comprehensive, insider information you need for the latest version of Ruby on Rails. The new edition of this award-winning classic is completely updated for Rails 6 and Ruby 2.6, with information on system testing, Webpack, and advanced JavaScript. Ruby on Rails helps you produce high-quality, beautiful-looking web applications quickly - you concentrate on creating the application, and Rails takes care of the details. Rails 6 brings many improvements, and this edition is updated to cover the new features and changes in best practices."--